Następujące sumy algebraiczne zapisz w prostszej postaci. Oblicz wartość liczbową dla otrzymanych wyrażeń
1) 2x+x-3x
dla x=5

2) -2m-2a+3a-2m
dla m=-1 i a=1

3) 4c²-2a+5c²+6-5a
dla c=-1 i a=2

4) -9xy+8x²y-xy²-7x²y+4
dla x=1 i y=-1​


Odpowiedź :

a) 2x + x - 3x = 0

b) - 2m - 2a + 3a - 2m = -4m + a = -4 * (-1) + 1 = 4 + 1 = 5

[tex]c) 4c^{2}-2a+5c^{2}+6-5a = 9c^{2}-7a+6 = 9 * (-1)^{2}-7*2+6 = 9 - 14+6=1[/tex]

[tex]d)-9xy+8x^{2}y-xy^{2}-7x^{2}y+4= -9xy+x^{2}y-xy^{2}+4 = -9*1*(-1) + 1^{2}*(-1)-1*(-1)^{2}+4=9-1-1+4=11[/tex]

:)